Implications of Regional Regulations Cancellation Based on Law Number 23 of 2014 about Local Government and Law Number 5 Of 2004 about The Supreme Court - Saragih, Hohen (NAJAHA, 2023)
Cancellation of Regional Regulations is the authority of the government represented by the Supreme Court in carrying out the supervisory function both preventively and repressively. The annulment function is carried out to provide legal certainty so that the law can have a strong meaning and identity. The purpose of this research is to produce a strong understanding of the mechanism for cancelling regional regulations by the Supreme Court on the basis of filing a judicial review of the materials of regional rules that have been running and their implications for legal certainty. The method used in this study is a normative juridical method through a review of the literature, which is considered relevant to this research. Based on the results of this study, it was concluded that the mechanism for implementing the Supreme Court's decision regarding the cancellation of the Regional Regulation as stated in Article 8 paragraph (2) of Supreme Court Regulation No. 1 of 2011, followed up by implementing the decision no later than ninety days after the decision was sent to the Regional Government. The implication is that the cancellation of a regulation by the Supreme Court directly or indirectly has binding legal force.